Analisis Determinan Timeliness Of Corporate Internet Reporting - Rafie Akbar Sumarno; Muhammad Husni; Rizky Aldi Setianda; Haris Reza Fathony; M. Fahriyal Aldi; Kurniawan Harminsyah B; Ardi Kurniawan (Universitas Pahlawan Tuanku Tambusai, 2026)
This investigation endeavors to generate empirical substantiation pertaining to the effects of liquidity, firm dimensions, and profitability upon the promptness of corporate web-based reporting through utilization of statistical software SPSS paired with logistic regression methodology, implemented across transportation-sector enterprises registered on the Indonesia Stock Exchange, encompassing an analytical sample derived from 100 observations obtained from 25 companies throughout the 2022–2025 timeframe. The investigation's outcomes demonstrate that firm size and profitability have a significant and positive effect on the timeliness of corporate internet reporting, whereas the liquidity dimension fails to manifest a statistically consequential relationship in relation to the timeliness of corporate internet reporting.